2021
DOI: 10.1371/journal.pone.0245626
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of microbial communities and soil nutrients in sugarcane rhizosphere soil under water soluble fertilizer

Abstract: The dynamics of soil microbial communities are important for plant health and productivity. Soil microbial communities respond differently to fertilization. Organic water soluble fertilizer is an effective soil improver, which can effectively improve soil nutrient status and adjust soil pH value. However, little is known about the effects of water soluble fertilizers on soil microbial community, and the combined effects on soil nutrients and sugarcane productivity. Therefore, this study sought to assess the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 57 publications
7
19
0
Order By: Relevance
“…significantly improved crop yields. Soil depth is an important environmental gradient [46][47][48], as well as soil amendmet practices affecting soil physio-chemical properties [49][50][51][52]. In the current study, soil OM, TC, NH 4 + NO 3…”
Section: Plos Onementioning
confidence: 79%
“…significantly improved crop yields. Soil depth is an important environmental gradient [46][47][48], as well as soil amendmet practices affecting soil physio-chemical properties [49][50][51][52]. In the current study, soil OM, TC, NH 4 + NO 3…”
Section: Plos Onementioning
confidence: 79%
“…Currently, face a challenge in finding an effective balance between N input and crop N requirements to achieve high crop yields while maintaining soil quality and reducing the environmental footprint (Lassaletta et al 2014 ; Zhang et al 2015 ). Niu et al ( 2021 ) found that water soluble fertilizer affected the enrichment of microorganisms by improving the nutrient content of the soil, thereby affecting the growth and yield of sugarcane. Meanwhile, Compton et al ( 2004 ) also found that soil microbial biomass decreased with the application of nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…This contributes to interspecies relationships and interpopulation relationships, which promotes a healthy and optimum environment for plant growth [59]. In addition, the composition and diversity of these soil microbial communities are important indicators of the soil fertility level [60]. The CFSF1-treated soils show a more diverse profile of AOA, namely Nitrososphaeraceae (42%), Candidatus Nitrososphaera (25%), and other small percentage of the members of Nitrosospumilaceae (Figure 7B).…”
Section: Abundance Of Nitrifying Bacteria and Archaea In Sf-treated S...mentioning
confidence: 99%